Marasmius and allied genera in forest communities of the Białowieża National Park - Maria Lisiewska (Acta Mycologica, 2014)
Distribution of 13 species of Marasmius and allied genera on a permanent research plot in different forest communities is demonstraled on maps. The following species were taken into account: Marasmius androsaceus, M. bulliardii, M. chordalis, M. cohaerens, M. epiphyllus, M. lupuletorum, M. recubans, M. rotula, M. scordonius, M. splachnoides, M. wynnei, Marasmiellus ramealis and Micromphale perforans.